The hallmark domain of the oldest autophagy receptor family is a cargo-binding module. Issue 4 (3rd April 2023) - Pan, Zhao-Qian; Ye, Keqiong; Du, Li-Lin
ABSTRACT: In selective macroautophagy/autophagy, autophagy receptors are key molecules that determine cargo specificity. Most known autophagy receptors only exist in some but not all eukaryotic lineages. The exception is Nbr1 proteins, which are conserved across eukaryotes. The four-tryptophan (FW) domain is the hallmark of Nbr1 proteins, but its function has been unknown. Our recent study found that the FW domain in the Nbr1 protein of the filamentous fungus Chaetomium thermophilum binds the α-mannosidase Ams1, a known selective autophagy cargo in budding yeast and fission yeast. Furthermore, we showed that when C. thermophilum Nbr1 and Ams1 are expressed heterologously in fission yeast, FW domain-mediated binding can promote autophagic delivery of Ams1 into vacuoles. We solved the structure of the FW-Ams1 complex and revealed the structural mechanism underlying Ams1 recognition by the FW domain. The N -terminal di-glycine peptide of Ams1 fits into a conserved pocket of the FW domain. We propose that this cargo-binding mechanism may also be employed by Nbr1 proteins in other eukaryotes.